Impact of Transport Method in Patients With ST‐Segment–Elevation Myocardial Infarction on Patient Outcomes: Real‐World Data From the ACSIS Registry - Aviad Rotholz; Tsahi T. Lerman; Jenan Awesat; Alon Eisen; Roy Beigel; Elias Kanani; Omri Braver; Katia Orvin (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The ambulance system is vital for the early management of patients with ST‐segment–elevation myocardial infarction, reducing delays in diagnosis and treatment. This study examined the impact of transport mode on reperfusion therapy and mortality among patients with ST‐segment–elevation myocardial infarction from 2000 to 2021. Methods Data from the ACSIS (Acute Coronary Syndrome Israeli Survey) registry 2000 to 2021 were analyzed. Three transport methods of patients with ST‐segment–elevation myocardial infarction were evaluated. The impact on patient outcomes was assessed. Temporal trends from early (2000–2010) and late (2013–2021) periods were compared. Results Of 8035 patients with ST‐segment–elevation myocardial infarction, 52.9% were transported by mobile intensive care units, 13.1% by basic life support ambulances, and 34% self‐transported. Use of mobile intensive care units increased from 48.7% to 60.9% (P<0.001), while self‐transport decreased from 36.8% to 28.7% (P<0.001). Time from hospital arrival to primary percutaneous coronary intervention significantly decreased for mobile intensive care unit patients (60 to 36 minutes; P<0.001) and for basic life support patients (90 to 73 minutes; P=0.002), while self‐transport showed no significant change. Adjusted analysis revealed a decrease in 30‐day major adverse cardiovascular events (odds ratio, 0.53; P<0.001) and 1‐year mortality rates (hazard ratio, 0.84; P<0.05) for the entire cohort with no difference within or upon comparing transport methods between periods. Primary percutaneous coronary intervention rates and guideline‐directed medical therapy also rose significantly (P<0.001). Conclusions Improved major adverse cardiovascular event and mortality rates are attributed to enhanced in‐hospital and postdischarge care, including primary percutaneous coronary intervention and guideline‐directed medical therapy rather than transport improvements, although these contribute to more stable arrival conditions.